GDF11 restricts aberrant lipogenesis and changes in mitochondrial structure and function in human hepatocellular carcinoma cells. Issue 5 (10th November 2020) - Hernandez, Sharik; Simoni‐Nieves, Arturo; Gerardo‐Ramírez, Monserrat; Torres, Sandra; Fucho, Raquel; Gonzalez, Jonathan; Castellanos‐Tapia, Lyssia; Hernández‐Pando, Rogelio; Tejero‐Barrera, Elizabeth; Bucio, Leticia; Souza, Verónica; Miranda‐Labra, Roxana; et al.
Abstract: Growth differentiation factor 11 (GDF11) has been characterized as a key regulator of differentiation in cells that retain stemness features. Recently, it has been reported that GDF11 exerts tumor‐suppressive properties in hepatocellular carcinoma cells, decreasing clonogenicity, proliferation, spheroid formation, and cellular function, all associated with a decrement in stemness features, resulting in mesenchymal to epithelial transition and loss of aggressiveness. The aim of the present work was to investigate the mechanism associated with the tumor‐suppressive properties displayed by GDF11 in liver cancer cells. Hepatocellular carcinoma‐derived cell lines were exposed to GDF11 (50 ng/ml), RNA‐seq analysis in Huh7 cell line revealed that GDF11 exerted profound transcriptomic impact, which involved regulation of cholesterol metabolic process, steroid metabolic process as well as key signaling pathways, resembling endoplasmic reticulum‐related functions. Cholesterol and triglycerides determination in Huh7 and Hep3B cells treated with GDF11 exhibited a significant decrement in the content of these lipids. The mTOR signaling pathway was downregulated, and this was associated with a reduction in key proteins involved in the mevalonate pathway. In addition, real‐time metabolism assessed by Seahorse technology showed abridged glycolysis as well as glycolytic capacity, closely related to an impaired oxygen consumption rate and decrement in adenosine triphosphate production. Finally, transmission electron microscopy revealed mitochondrial abnormalities, such as cristae disarrangement, consistent with metabolic changes. Results provide evidence that GDF11 impairs cancer cell metabolism targeting lipid homeostasis, glycolysis, and mitochondria function and morphology. Abstract : GDF11 constrains aberrant lipid metabolism GDF11 induces mitochondrial structural changes and function Mitochondrial changes were related to a decrease in oxygen consumption rate.